Polymers as sensing layers in MEMS biosensors for molecular diagnosis - Niranjan, Arpana; Gupta, Pallavi; Rajoria, Manisha; Noor, I. M. (John Wiley and Sons, 2025)
Polymers have been used significantly in MEMS (micro-electro-mechanical systems) biosensors as substrates, sensor materials, packaging, surface encapsulation, and transducer elements. The sensing layer is a component that interacts with the target molecule. The choice of material for the sensing layer affects the sensitivity of the sensor. This research explores four commonly used polymers (polydimethylsiloxane (PDMS), nylon, poly methyl methacrylate) (PMMA), and polyethylene) as a sensor layer for bio-recognition in MEMS biosensors. The study is simulation-based. Two models, namely, a simple micro-cantilever beam and piezoelectric cantilever MEMS, are regarded in the paper. Different properties, such as stress and displacements, are studied, as well as voltage, in the case of the piezoelectric model. The comparative study contributes to understanding how different polymer materials and readout methods impact the choice of material for the sensing layer for MEMS biosensors. Results show that for applications using displacement measurement for further analysis, a simple cantilever is more suitable. The PED model has low displacement sensitivity but is an excellent choice when electric output is required. PDMA shows the best results among the materials used for comparative analysis. The final choice of materials depends on the specific application; PDMA provides flexibility and ease of fabrication, whereas PMMA is more suitable for applications requiring rigidity and chemical resistance. PDMA has 1.63 times more voltage sensitivity than PMMA. Furthermore benefits and challenges of using polymer as a sensing layer are also discussed.